2012
DOI: 10.1097/aog.0b013e31826af4fe
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Endometrial Ablation Device Complications and Use Outside of the Manufacturersʼ Instructions

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…More serious complications may include bowel injury, cardiac arrest, urinary tract injury, carbon dioxide embolus, sepsis, and death 45. It is recognized that inappropriate use and physician error are contributors to device-related complications 44,46. In the most recent review of the Manufacturer and User Facility Device Experience (MAUDE) database, Brown and Blank noted the possibility of false tracking with the NovaSure device leading to transmural thermal injury, thus highlighting the importance of on-label use of the device and proper technique in deployment and seating procedure 46…”
Section: Safety Of Novasure Endometrial Ablationmentioning
confidence: 99%
“…More serious complications may include bowel injury, cardiac arrest, urinary tract injury, carbon dioxide embolus, sepsis, and death 45. It is recognized that inappropriate use and physician error are contributors to device-related complications 44,46. In the most recent review of the Manufacturer and User Facility Device Experience (MAUDE) database, Brown and Blank noted the possibility of false tracking with the NovaSure device leading to transmural thermal injury, thus highlighting the importance of on-label use of the device and proper technique in deployment and seating procedure 46…”
Section: Safety Of Novasure Endometrial Ablationmentioning
confidence: 99%
“… 4 Both of the endometrial ablation systems used in the current study provide the level of safety expected of modern endometrial ablative procedures, although the NovaSure system has a much longer record of post-market safety surveillance. 17 , 33 The number of AEs in the current study was low and did not significantly differ between treatments. Two serious AEs occurred in the NovaSure group (vaginal bleeding and fever with pain), and one occurred in the Minerva arm (renal failure secondary to dehydration).…”
Section: Discussionmentioning
confidence: 52%
“…Based on the available information, 66 of the 829 adverse events (8%) occurred when the endometrial ablation was performed outside of the labeled instructions for use of the procedure. The total number of endometrial ablations performed during this time period was not reported by the authors; therefore, the proportion of procedures with adverse events could not be determined from these data [39].…”
Section: Hysteroscopic Devicesmentioning
confidence: 92%
“…In 2012, Brown and Blank analyzed adverse events associated with endometrial ablation procedures that were reported in the FDA's Manufacturer and User Facility Device Experience (MAUDE) database [39]. A total of 829 adverse events were reported between 2005 and 2011.…”
Section: Hysteroscopic Devicesmentioning
confidence: 99%